Humanizing education: self evaluation (muhasabah) - Che Mohd Salleh, Marhanum (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
This chapter discusses three important points in Surah Al-Hasyr verse 18 to do self reflection. "O you who believe! Have Taqwa of Allah and let every person look to what he has sent forth for tomorrow, and fear Allah. Verily, Allah is All-Aware of what you do.)